SAT0388 Mood Disorders in Systemic Lupus Erythematosus (SLE): Results from an International, Inception Cohort Study. (9th June 2015) - Hanly, J.G.
Abstract : Background: Neuropsychiatric (NP) events in patients with SLE include mood disorders. Objectives: To determine the frequency, characteristics, clinical and autoantibody associations of mood disorders in a large, multi-ethnic/racial, inception cohort of SLE patients. Methods: A prospective study of new onset SLE patients was performed by an international network of 32 academic centers in 11 countries. Patients were evaluated at enrollment and annually for up to 14 years. Data were collected at each assessment on demographic and clinical manifestations, medications, SLE disease activity index-2000 (SLEDAI-2K) and Systemic Lupus International Collaborating Clinics (SLICC)/ACR damage index (SDI). Nervous system events were recorded using the ACR case definitions for 19 NP syndromes. These include mood disorders, determined by clinical judgment (based on Diagnostic and Statistical Manual, DSM-IV, criteria) and consisting of: (i) major depressive-like episode, (ii) mood disorder with depressive features, (iii) mood disorder with manic features and (iv) mood disorder with mixed features. Lupus anticoagulant, IgG autoantibodies to cardiolipin, β2 -glycoprotein I, ribosomal P and NMDA glutamate receptor 2 were measured at enrollment. Pre-defined rules determined the attribution of NP events to SLE and non-SLE causes. Cox regression was used to examine the associations of various factors with the occurrence of first mood disorder and first SLE-attributed mood disorder. Results: Of 1, 827 SLE patients, 88.9% were female, 48.9% Caucasian with mean ± SD age 35.1±13.3 years. At enrollment, mean SLE duration was 5.6±4.8 months, SLEDAI-2K was 5.3±5.4, SDI was 0.31±0.74. The mean follow-up was 4.73±3.45 years. Over the study 863 (47.2%) patients had 1, 627 NP events of which 503 (30.9%) were attributed to SLE. Mood disorders were the second most frequent NP event: 232 patients experienced 256 mood disorders of which 98/256 (38.3%) were attributed to SLE. The predominant mood disorders were major depressive-like episodes [134/256 (52.3%)], followed by mood disorder with depressive features [114/256 (44.5%)] and the remaining two mood disorders accounted for only 8/256 (0.03%) events. The estimated cumulative incidence of any mood disorder and any SLE-attributed mood disorder after 10 years was 17.7% (95%CI=[15.1%, 20.2%]) and 7.9% (95%CI=[6.0%, 9.9%]), respectively. A total of 110/256 (43.0%) mood disorders occurred in isolation without other concurrent NP events. Multivariate regression revealed a greater risk of mood disorder in patients with other concurrent NP events (p≤0.01) and a lower risk with Asian race/ethnicity (p=0.01) and immunosuppressive drugs taken in the absence of antidepressants (p=0.003). No association was found between mood disorders and SLEDAI-2K, SDI scores or lupus autoantibodies, whether or not the analysis was confined to mood disorders attributed to SLE. Conclusions: Mood disorders are the second most frequent NP event in SLE patients and about one third are attributable to lupus. The lack of association of most mood disorders with global SLE disease activity, cumulative organ damage and lupus autoantibodies emphasize their multifactorial etiology and a role for non-lupus specific therapies. Disclosure of Interest: None declared